Agro-ecological terroir units in the North West Iberian Peninsula wine regions. (June 2019) - Cardoso, Andreia Saavedra; Alonso, Joaquim; Rodrigues, Ana Sofia; Araújo-Paredes, Cláudio; Mendes, Susana; Valín, Maria Isabel
Abstract: Viticultural zoning studies that support the definition of terroir units general follow two main approaches of geographic differentiation related either to: a) land capability or vineyard suitability, or b) grape, grapevine or wine characteristics. Both approaches are commonly considered in the definition of terroir at regional and local approaches. The purpose of this preliminary study was to develop and apply a methodology for viticultural zoning in order to establish the basis of studies on wine typicality. This will allow to question and compare the existent Protected Designations of Origin (D.O.) in the North West Iberian Peninsula wine regions (North of Portugal and Galicia-Spain). The assessment of Agro-ecological Terroir Units for viticulture includes climate and soil environmental factors selected for their relevance at regional scale, with the use of state-of-the-art variables and indices appropriate for the specified regions. The methodology considers the International Organisation of Vine and Wine guidelines (OIV, 2012), it is based upon the development of a Geographic Information System (GIS) and uses multivariate zoning with principal component analysis and clustering procedures. The results suggest that the sub-regions of Monção e Melgaço and Rías Baixas are integrated in a different terroir unit from the other Minho Sub-regions, which could give way to further inquiry with the purpose of reclassification based on studies on quality and typicality for the Alvarinho Wine. This regional and national cross-border classification provides a useful framework for territorial and viticultural policies with further validation at local and farm scales. This validation includes experimental surveys in selected vineyards for geographic differentiation of wine profiles and for supporting precision viticulture at plot and landscape scale. Highlights: A methodology of agro-ecological zoning for viticulture was developed using multivariate geographic clustering. The 12 agro-ecological terroir units (ATU) obtained represent areas of similar vine-relevant environmental conditions. These ATU were defined and described using climate and terrain environmental indexes or relevant factors. This study allows to draw similarities/differences between different Viticultural regions and sub-regions. The results can ground a study on the typicality for the Alvarinho variety through the differentiation of wines.